(untitled) (Damascus University Journal for the economic and Political sciences, 2026)
The concept of Iraqi national security is considered one of the complex concepts that is no longer limited to traditional military and border aspects alone, but has extended to include vital dimensions that affect the core of citizens’ lives and the stability of the state. In light of accelerated climate changes and global health crises, unconventional threats — "epidemic and environmental" — have emerged as pressing elements that surpass the capabilities of conventional weapons to confront. Iraqi national security represents the state’s ability to protect its entity, interests, and values from external and internal threats. With the development of the international environment, the focus has shifted from "state security" in its narrow sense to "human security," where the availability of water, the safety of food, and protection against epidemics have become essential pillars no less important than border protection. Environmentally, Iraq ranks among the five countries in the world most affected by climate change. These threats are not merely natural phenomena; they are drivers of political and social instability. Regarding epidemic threats, the Corona pandemic and other epidemics (such as hemorrhagic fever and cholera) have demonstrated that health security is an integral part of national security, as the state is forced to allocate budgets. Since 2003, the mindset of the decision-maker in Iraq tends to try to formulate the strategic construction of national security, and in the same context, what strengthens national security is that the entire national approach tries to find a security approach capable of dealing with the various internal and external challenges that affect Iraqi national security in particular. Those challenges whose impact and continuity are linked to external regional and international projects.